Trends in Assistive Technologies - Rafael Garcia-Ramirez, Alejandro (Biomedical Engineering, 2023)
This book covers a wide range of subject areas, including assisted living, social robots, augmentative and alternative communication, connectivity, artificial intelligence, and robot design. Each chapter is authored by experts in their respective fields and offers readers theoretical and applied scientific papers that can serve as original research or review papers. This valuable volume is essential for researchers, practitioners, and anyone interested in developments in assistive technology. It explores trends and innovations in the field, demonstrating how assistive technology is enhancing the lives of people with disabilities or reduced mobility, and the elderly. The book is a comprehensive overview of the latest research and advancements in assistive technology, making it an essential addition to any library for both seasoned researchers and those just starting to explore the field. We are grateful to the authors for their invaluable contributions to this book, which would not have been possible without their generosity in sharing their knowledge and experiences.